Predicting Interatrial Septum Rotation: Is the Position of the Heart or the Direction of the Coronary Sinus Reliable?. Issue 4 (14th February 2015) - SUN, HUAN; WANG, YANJING; ZHANG, ZHENMING; LIU, LIN; YANG, PING
<x xml:space="preserve">Abstract</x> Background Determining the location of the interatrial septum (IAS) is crucial for cardiac electrophysiology procedures. Empirical methods of predicting IAS orientation depend on anatomical landmarks, including determining it from the direction of the coronary sinus (CS) and the position of the heart (e.g., vertical or transverse). However, the reliability of these methods for predicting IAS rotation warrants further study. The purpose of this study was to assess the clinical utility of the relationship between IAS orientation, CS direction, and heart position. Methods Data from 115 patients undergoing coronary computed tomography (CT) angiography with no evidence of cardiac structural disease were collected and analyzed. Angulations describing IAS orientation, CS direction, and heart position were measured. The relationships between IAS orientation and each of the other two parameters were subsequently analyzed. Results The mean angulations for IAS orientation, CS direction, and heart position were 36.8 ± 7.3° (range 19.1–53.6), 37.7 ± 6.6° (range 21.3–50.1), and 37.1 ± 8.3° (range 19.2–61.0), respectively. We found a significant correlation between IAS orientation and CS direction (r = 0.928; P < 0.01), and the linear regression equation was drawn: IAS orientation = 2.01 + 1.03 × CS direction (r2 = 0.86). No correlation was observed between IAS orientation and heart position (P = 0.86). Conclusion In patients without structural heart disease, CS direction may be a reliable predictor of IAS orientation, and may serve as a helpful reference for clinicians during invasive electrophysiological procedures. Further study is warranted to clarify the relationship between IAS orientation and heart position.